Decision support systems: Present and future - Lhotská, Lenka (European Journal for Biomedical Informatics, 2018)
Background: Information and communication technologies have become inevitable and an almost inseparable part of our lives. They have also penetrated many application areas including medicine. Objectives: The paper demonstrates the importance of correctly understanding the terms data, information and knowledge that represent the core of decision support and decision making processes. Methods: In the paper we describe the development of decision support systems from the first generation using a simple knowledge representation up to complex distributed solutions. Results: Based on the purpose, we identify three major groups of systems, namely recommendation, decision support and decision making systems. Conclusion: We summarize the development of decision support systems and estimate the future directions.
Keywords: Decision Support Systems, Clinical; systémy pro podporu klinického rozhodování